The recurrence of Bowen’s disease after topical 5% 5-fluorouracil cream application: A systematic review - Antoniman, Mohammad Agassi; Anggraini, Ika (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Bowen’s disease (BD) may develop into cutaneous squamous cell carcinoma (CSCC), which can spread to other parts of the body. 5% 5-fluorouracil (5-FU) cream is commonly used for topical therapy on BD; however, the frequency and duration of treatment per cycle have not been standardized. This systematic review aimed to identify the most effective frequency and duration of 5% 5-FU treatment for achieving complete clearance or minimal recurrence. Methods: A literature search was conducted using three electronic databases (PROSPERO ID: CRD42024607488): MEDLINE, Cochrane, and Scopus. The articles were selected based on their relevance to the clinical question. Appraisals were conducted using the Newcastle-Ottawa Scale and the revised Cochrane risk-of-bias tool for randomized trials. Results: Five selected studies with 550 participants were critically reviewed; two were cohort studies and three were randomized trials. Some patients in total studies used more than one therapy cycle. Four of the five studies showed a recurrence rate in 12 months after the end of treatment. In cohort studies, the recurrence rate was 0–8.3% with twice-daily application for 9–16 weeks, whereas in randomized trials, the recurrence rate was 14.3–27.3% with various application frequencies for 4 weeks. Conclusion: The most suitable duration and frequency of 5% 5-FU cream application per cycle to minimize the recurrence rate of BD is twice daily for four weeks per cycle. However, other factors may affect the recurrence rate.